HUBUNGAN TINGKAT PENDIDIKAN DENGAN PERILAKU MEROKOK DENGAN PERILAKU MEROKOK PADA KARYAWAN LAKI-LAKI UNIVERSITAS BATAM - Rusdani .; Nopri Esmiralda (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
This research is motivated by very poor smoking habits in Indonesia. On the other hand, the medical problems caused by this habit are numerous. Smokers are susceptible to diseases. In a previous study in Central Jakarta, it was stated that there was a positive relationship between health status and education level of a person. In different and more specific objects, this study aims to determine the relationship of a person's education level with smoking behavior. This research was conducted with quantitative research methods, using analytical research designs with cross-sectional approach conducted in January 2019. The research sample consisted of 42 male employees. Data was collected using a questionnaire. The analysis used in this study uses univariate analysis with frequency distribution, and bivariate analysis using chi-square statistical tests. Based on these methods, the results showed that as many as 33 respondents (78.6%) had undergraduate education levels and 33 respondents (78.6%) had smoking behavior. Based on statistical tests it is known that there is a significant relationship between education level and smoking behavior in male employees with p-value = 0.018 (p <0.05). From the results of the study it can be concluded that there is a significant relationship between the level of education with smoking behavior in male employees.